Language and Identity of Aviation Security - Pinem, Yune Andryani; Gultom, Mega Agustina; Sari, Nanik Rianandita (Sekolah Tinggi Teknologi Kedirgantaraan, 2024)
The Aviation Security (AVSEC) officers must navigate the complex interaction of maintaining authority while demonstrating politeness in their communication with passengers. This research explores how aspects of language proficiency for interaction are used by AVSEC officers to balance these roles and construct their professional identity. The research problem addresses how interaction proficiency serves both the functional need for authority and the relational need for politeness. The objective of the study is to identify the markers that contribute to this balance on communication effectiveness. Employing qualitative analysis, data were collected through recordings, observation and in depth interview of AVSEC officers at several workload simulations. The study finds that effective communication in AVSEC relies on a blend of clear verbal instructions and strong non-verbal cues to manage interactions smoothly and professionally. Officers must respond quickly, clarify when necessary, and interpret both verbal and non-verbal signals to prevent misunderstandings and uphold security. AVSEC officers balance authority with courtesy, using direct language and body language to ensure passenger cooperation, safety, and comfort.